-(8y+1)-(-7y-2)=0

Simple and best practice solution for -(8y+1)-(-7y-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y+1)-(-7y-2)=0 equation:


Simplifying
-1(8y + 1) + -1(-7y + -2) = 0

Reorder the terms:
-1(1 + 8y) + -1(-7y + -2) = 0
(1 * -1 + 8y * -1) + -1(-7y + -2) = 0
(-1 + -8y) + -1(-7y + -2) = 0

Reorder the terms:
-1 + -8y + -1(-2 + -7y) = 0
-1 + -8y + (-2 * -1 + -7y * -1) = 0
-1 + -8y + (2 + 7y) = 0

Reorder the terms:
-1 + 2 + -8y + 7y = 0

Combine like terms: -1 + 2 = 1
1 + -8y + 7y = 0

Combine like terms: -8y + 7y = -1y
1 + -1y = 0

Solving
1 + -1y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -1y = 0 + -1

Combine like terms: 1 + -1 = 0
0 + -1y = 0 + -1
-1y = 0 + -1

Combine like terms: 0 + -1 = -1
-1y = -1

Divide each side by '-1'.
y = 1

Simplifying
y = 1

See similar equations:

| sin(8x)=1 | | 4/9Y-1.4 | | 6x-2=6(X-7) | | 3+4(1+5)=31 | | 180(3-2)=s | | 5(x+1.67)=4x | | 202=1.2(-1.16)-3.8 | | 4(-9+x)=-24 | | 1/5(1)-2(-5)=1 | | -6-4=4x+4-3x | | 6[6-(-5x-3)]=270x+198 | | -4+x=-4 | | 1/5(5)-2(-1)=5 | | -1/3+(-1/2) | | 2x+36=3+8x-9 | | log(4k-5)=log(2k-1) | | -1/4(4)-2 | | 4/6x=2/9 | | -6-4=4x+4-3c | | 5(-4x+8)=-180 | | x+.75= | | 22/5p=10 | | 4=22+b/9 | | -1/5=37/5+2 | | -1/3+7/8 | | 4x+14=2x+10 | | 6x+72+2x+28=180 | | 5m-0=3m+7 | | -13+16=m-2 | | 2(2)=1-4 | | 5x-4=-x-10 | | 4x+6=7.2 |

Equations solver categories